Comparison of ballistic and strength training on swimming turn and dry-land leg extensor characteristics in elite swimmers - Jones, J. V.; Pyne, D. B.; Haff, G. G.; Newton, R. U. (International Journal of Sports Science & Coaching, 2018)
Swimmers undertake dry-land resistance training as part of their overall training regime in order to increase lower body force output, impulse and swim turn performance. We investigated whether short-term ballistic training or maximal strength training is more effective in enhancing leg extensor force characteristics during the swim turn. Twelve elite swimmers (10 males and 2 females 19.4 ± 1.0 y) were assigned to either strength (n = 6) or ballistic leg extensor (n = 6) training based on their coaching group for a six-week period. All testing was conducted during the final training cycle towards the World Championships selection trials. Swimmers undertook dry-land testing of a squat jump on a portable force platform with bodyweight only and an additional 30 kg load for males and 20 kg load for females. On the same day, all swimmers performed a turn analysis using a fixed force platform within the pool wall. There were no substantial differences between the strength and ballistic groups after the six-week intervention. Only squat jump peak velocity (loaded) showed a moderately large standardized difference (-0.71, ± 0.42 m/s) after six weeks in the strength-trained group. Relative peak power (4.0 ± 2.1 W/kg), squat jump peak force (loaded and unloaded) (195.0, ± 122.8 N; 155.0, ± 152.3 N), and squat jump impulse (unloaded) (2.9, ± 2.1 N) all showed small and clear improvements with ballistic training over the six-week intervention. Both strength and ballistic dry-land training can improve aspects of the push-off stage of the swim turn providing programming options for swimming and strength and conditioning coaches. ABSTRACT FROM AUTHOR